1999
DOI: 10.1002/(sici)1098-2396(199902)31:2<151::aid-syn8>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the GABAb receptor in gamma vinyl-GABA's inhibition of cocaine-induced increases in nucleus accumbens dopamine

Abstract: Previously, we demonstrated that gamma vinyl-GABA (GVG, Vigabatrin) dose-dependently inhibits cocaine-induced increases in dopamine (DA) concentrations in both the rodent and primate brain. Furthermore, it abolishes cocaine self-administration and conditioned place preference, while having no effect on locomotor activity or drug delivery to the brain. In an effort to better understand the mechanisms underlying this inhibition, we examined the effect of the selective GABA(B) receptor antagonist SCH 50911 on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Similar effects for baclofen have been reported for other addictive drugs such as alcohol, nicotine, and heroin 60–62. Furthermore, administration of vigabatrin, which elevates levels of endogenous GABA, reduces intake of heroin and cocaine in rats 63, 64…”
Section: Drug Addictionsupporting
confidence: 61%
“…Similar effects for baclofen have been reported for other addictive drugs such as alcohol, nicotine, and heroin 60–62. Furthermore, administration of vigabatrin, which elevates levels of endogenous GABA, reduces intake of heroin and cocaine in rats 63, 64…”
Section: Drug Addictionsupporting
confidence: 61%
“…GABA B receptors are one of the most abundant classes of receptors in the CNS (Bischoff et al 1999;Margeta-Mitrovic et al 1999), and thus it is difficult to identify a particular locus of action for their role in cocaine reinforcement. It has been postulated that GABA B agonists produce their effects on cocaine self-administration by attenuating cocaine-induced increases in nucleus accumbens dopamine (Ashby et al 1999). Dopamine release in the accumbens is under tonic inhibitory control by GABAergic interneurons that make synaptic contact with dopaminergic cell bodies in the ventral tegmental area, and we have previously reported that intra-VTA baclofen attenuates cocaine self-administration (Brebner et al 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…These researchers also found that baclofen administered directly into the NA or VTA also suppressed responding maintained under an FR5 schedule of cocaine infusion. Further, the indirect agonist gamma-vinyl GABA attenuated the increases in extracellular DA in the NA produced by IP injection of cocaine, and this effect was reversed by co-administration of SCH 50911, a GABA B antagonist (Ashby et al 1999). Taken together, these data suggest that the activity of GABAergic innervation of the NA and VTA functions to inhibit DA release in these areas, thereby possibly attenuating the reinforcing efficacy of cocaine.…”
Section: Discussionmentioning
confidence: 99%